Role of the jejunum versus ileum on intestinal gas dynamics during a balanced meal in healthy subjects - Harder, Hermann; Hernando-Harder, Ana C.; Franke, Andreas; Krammer, H.; Singer, Manfred V. (Digestive diseases and sciences, 2006)
Under physiological conditions, the human gut adapts intestinal gas propulsion and evacuation to prevent intestinal gaseous complaints In this study we aimed to determine influences of the jejunum versus ileum on intestinal gas dynamics during a balanced meal. Paired studies were randomly performed with seven women and three men, ages 28-42. A mixed liquid meal was infused (1 kcal/min) into the duodenum. After 30 min, gas was infused (12 ml/min) into the jejunum or ileum for 150 min. Gas expulsion was measured, and perception and girth changes were assessed. Postprandial intestinal gas propulsion was uneventful and recovery complete, with −7± 58 and −92± 44 ml final intestinal gas retention for jejunal and ileal gas infusion, respectively. Neither significant differences in abdominal perception nor changes in abdominal girth were seen. During a balanced meal, intestinal gas is effectively propulsed aborally, and this does not depend on the site of the small intestinal stimulation.